Early menarche and mental health: Are we addressing the real burden in Pakistan? - Mariam Mubashir (Journal of the Pakistan Medical Association, 2026)
Dear Editor, The age of menarche has been on a steady decline in Pakistan. ¹ A cross-sectional study conducted by the University of Faisalabad. ² thoroughly investigated and reported a significant association between early pubertal onset and increased vulnerability to depressive symptoms in Pakistani adolescent females. A recent international study conducted in China. ³ Suggests that if early age at menarche can be utilised as a biological marker for predicting depression in adolescent girls, it may allow for timely and targeted interventions such as mindfulness-based therapy. However, despite promising evidence, many critical questions remain unanswered, particularly in the domain of treatment and interventions available in Pakistan. Are paediatricians and general practitioners adequately trained to recognise the early signs of the psychological impact of early menarche? Are mental health counselling services available in school settings, particularly in the public sector? In a country already shrouded in stigma, the onset of early menarche in young adolescent females is almost always accompanied by confusion, shame, fear, and isolation. With a lack of support from home, little to no guidance provided by schools, and inadequate mental health screening and targeted interventions available in paediatric clinics and hospitals, their psychological burden may be intensified. It is essential to bear in mind that puberty is already a critical and vulnerable period in the life of a young adolescent female. Without targeted interventions, there is a legitimate concern that these issues will worsen, further marginalising adolescent girls and adversely affecting their mental, emotional, and physical well-being. It is about time our Pakistani paediatricians, psychologists, educators, and public health officials came together to address and recognise early menarche as a potential psychological risk factor. Appropriate screening tools for physicians to recognise early signs of depression and the integration of psychological counselling services in schools are desperately needed. More funds should be invested in research and studies dedicated entirely to finding more interventional strategies, and last but not least, parental education is needed to encourage healthy discussions at home. A little care and support go a long way! Sincerely,